Saxophone adding a new dimension to Koli music - Mumbai Archive Project Team (Jio Institute, 2024)
While the saxophone is not traditionally a part of Koli music, its use in fusion styles demonstrates the adaptability and evolution of traditional musical forms. Incorporating Western instruments like the saxophone adds a new dimension to Koli music, creating a unique and dynamic sound that appeals to a wider audience.